Awakening giant : China's game plan in the last decade of the 20th century (1989-1999). - Ng, Lawrence. (2008)
This dissertation is a study of China's actions and reactions to counter perceived American and Japanese strategies of keeping it from achieving great power status during the last decade. From a careful reading of the speeches of Chinese leaders and party-approved articles as well as observing Chinese foreign policy conducted over the last decade, it is possible to find ample evidences to construct a "Chinese game plan" for countering American and Japanese threats.